(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Distal third fracture is the most common location. Treatments are conservative or surgical; improper indication will leave deformities that will affect the child’s pronation and supination function later on. Purposes: To compare the results of conservative and surgical treatment. Methods: This cross-sectional retrospective study was in patients ≤ 12 years old, treated at HTO for 5 years from March 2013 - April 2017. Results: The average follow-up time of our study is 43.3 ± 12.3 months, the shortest is 28 months, the longest is 78 months. According to Daruwalla criteria, surgical results in 100% bone healing and good functions, and conservative results in 1 case of limited pronation of the hand of 22˚; however, it was compensated by shoulder movement and did not require further intervention. “Very satisfied” conservation was statistically significantly higher than the surgery group (76.7% vs 43.3%, p=0.011). Conclusion: The bone healing rate of both treatment methods is high. Depending on the age, fracture type, fracture line, and displacement of each case as well as respecting the ability to remodel, choose the appropriate treatment method to give the best results.